Mild Alkaline Pretreatment on Sugarcane Bagasse: Effects of Pretreatment Time and Lime to Dry Bagasse Ratio: Mild Alkaline Pretreatment on Sugarcane Bagasse - Riadi, Lieke; Hansen, Yoelsando; Pratiwi, Jesslyn; Purwanto, Maria Goretti Marianti (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
Sugarcane waste is organic waste which has produced at about 8 × 106 tons annually in Indonesia. This lignocellulosic waste can be used as raw material for bioethanol manufacture through pretreatment, hydrolysis, and fermentation process. This study aims to evaluate system parameters of bagasse pretreatment using lime (Ca(OH)2) in a batch system and to obtain the yield (g/g) of glucose produced from pretreated bagasse via enzymatic hydrolysis. The variables used in this study were pretreatment time and lime ratio to bagasse in the pretreatment step. It was then followed by a hydrolysis step to produce glucose. The fermentation was conducted to investigate how much ethanol can be produced at the best glucose yield. The results showed that pretreatment time gave a stronger effect on the glucose yield compared to lime ratio to bagasse. Longer pretreatment time showed the increased glucose yield in the hydrolysis of pretreated bagasse. However, after 180 minutes of pretreatment, glucose yield was decreased. Meanwhile, a higher ratio of lime to bagasse in the pretreatment process reduced the glucose yield. The best glucose yield (0.071 g/g) was obtained from the pretreatment process with a ratio of 0.5 g Ca(OH)2 g–1 bagasse for 180 min; pH 5.0 and the ethanol content was (5.704 ± 0.15) g L–1.